Funcionalidad familiar y su relación con la autoestima de los niños y niñas de primer año de básica de la escuela "Vicente Bastidas Reinoso" de la ciudad de Loja. Periodo lectivo 2014 – 2015. Lineamientos propositvos - Cartuche Pasaca, Luis Alberto (2015)
This thesis refers to: FAMILY FUNCTION AND ITS RELATION TO BASIC FIRST YEAR CHILDREN SEL FESTEEM "VICENTE BASTIDAS REINOSO" LOJA CITY. ACADEMIC YEAR 2014 - 2015 SCHOOL PROPOSITIONAL GRIDEFINES. The general objective of this research was: To analyze the relationship of family functioning on self-esteem of children in the first year of basic education, school Vicente BastidasReinoso city of Loja. Scientific research is descriptive - analytical, allowing to determine the incidence of family functioning on self-esteem; deductive, analytical - inductive methods as we used synthetic, descriptive and statistical techniques and instruments, as applied: the test of family functioning and children's self-esteem scale; the sample population is 30 children and 30 parents. The application of the test of family functioning can conclude that 47% of the investigated belong to a moderately functional family, 23% are dysfunctional families, 20% are functional families and 10% are highly functional families, just so I applied the self-test is concluded that 33% of children have a regular self-esteem, 30% have good self-esteem, self-esteem 20% very good and 17% poor self-esteem. As a result of the investigation it was determined chelates family functioning is directly related to the level of self-esteem, so it should be strengthened assertive communication in family Dinamia, creating a suitable scenario to strengthen the self-esteem of children.